The Reality of Planning in The Iraqi Football Premier League From Coaches and Players’ perspective - abdulsattar, Mohannad; Makhlif, Abdulrahman (Journal of Physical Education, 2018)
The Reality of Planning in The Iraqi Football Premier League From Coaches and Players’ perspective Planning in a very important aspect in the field of sports especially in Iraqi football premier league. The importance of research lies in identifying the reality of planning the Iraqi premier league for football from the point of view of coaches and players. the problem of the research lies in the weakness of planning in some of the premier league for football in Iraq. The research used the descriptive method. The subjects were (120) coaches and players of the Iraqi premier league for football. The researcher deigned a questionnaire for the importance of planning in the Iraqi premier league football. The data was collected and treated using SPSS to come up with the conclusions. The researchers concluded that there is weakness in the administration of some Iraqi football premier league clubs especially in planning more than other section. Finally they recommended that the federation should pay attention to planning process as a basic requirement for the development of Iraqi football premier league.